COVID-19 Induced Immunosuppression resulting in Pulmonary Mucormycosis : A Long COVID sequalae (Journal of Medicine, 2021)
With increasing incidence of Severe Acute Respiratory Distress Virus 2(SARS -CoV -2) in India, there has been growing reports of super infections in post covid 19 period. Long COVID refers to persistence of COVID19 symptoms for weeks to months. While most common manifestation of long COVID is fatigue and ill health, it may lead to development of life-threatening complications like Pulmonary Mucormycosis. We report a case of 54 year young, non-diabetic previously healthy male who had moderate COVID19 treated with low dose steroids and recovered completely, only to present with hemoptysis 3 months later on High Resolution Computed Tomography Scan of the Chest and Rhizopus fungi on bronchoalveolar lavage confirming Post Covid Pulmonary Mucormycosis in non-immunocompromised host. Patient was managed with dual antifungal therapy intravenous Liposomal Amphotericin B and Posaconazole for 3 weeks, followed by oral Posaconazole.J MEDICINE 2021; 22: 150-154